Oceanic Island forests buried by Holocene (Meghalayan) explosive eruptions: palaeobiodiversity in pre-anthropic volcanic charcoal from Faial Island (Azores, Portugal) and its palaeoecological implications - Góis-Marques, C. A. (2022)
In Faial Island (Azores Archipelago, North Atlantic Ocean), charcoalified and mummified wood fossils have been reported within late Holocene (Meghalayan) pyroclastic deposits from the Caldeira Formation. Due to their re cent age, a detailed study conveys a snapshot into Azorean palaeophytodiversity and palaeovegetation, ca. 7–5 centuries before the arrival of Portuguese settlers to the Azores Islands. Here we provide the first detailed ana tomical and taxonomical study of these wood fossils. In total, 41 samples were collected from seven localities, mainly from a ~1200 yr BP ignimbrite. Field work revealed autochthonous and paraautochthonous assemblages, with tree trunks in upright position. The anatomical study of the fossil woods resulted in the identification of Juniperus brevifolia, Laurus azorica, Myrsine retusa, Morella faya, Picconia azorica, Prunus lusitanica subsp. azorica, and Vaccinium cylindraceum. Two fossil assemblages are comparable to the proposed potential natural vegetation (PNV) for the Azores. Surprisingly, P. lusitanica subsp. azorica was the second most abundant fossil wood suggest ing that this tree was more abundant in a recent past in Faial Island and probably in the archipelago. This is cor roborated by historical accounts, and its modern scarcity was certainly anthropically driven. Identifying Holocene plant macrofossils is essential to properly reconstruct oceanic islands terrestrial palaeoecosystems, especially where forests with high percentage of entomophilous taxa are underrepresented in palaeopalynological limnic record. Further work is necessary to reconstruct Faial Island and Azores archipelago palaeovegetation which is essential to provide an ecosystem base-line for restoration and management.